Asymptomatic COVID-19 in the elderly: dementia and viral clearance as risk factors for disease progression - Esteban, Ignacio; Bergero, Georgina; Alves, Camila; Bronstein, Micaela; Ziegler, Valeria; Wood, Cristian; Caballero, Mauricio T.; Wappner, Diego; Libster, Romina; Perez Marc, Gonzalo; Polack, Fernando P. (Gates open research, 2021)
Background: SARS-CoV-2 infected individuals ≥60 years old have the highest hospitalization rates and represent >80% fatalities. Within this population, those in long-term facilities represent >50% of the total COVID-19 related deaths per country. Among those without symptoms, the rate of pre-symptomatic illness is unclear, and potential predictors of progression for symptom development are unknown. Our objective was to delineate the natural evolution of asymptomatic SARS-CoV-2 infection in elders and identify determinants of progression. Methods: We established a medical surveillance team monitoring 63 geriatric institutions in Buenos Aires, Argentina during June-July 2020. When an index COVID-19 case emerged, we tested all other eligible asymptomatic elders ≥75 or >60 years old with at least 1 comorbidity. SARS-CoV-2 infected elders were followed for 28 days. Disease was diagnosed when any COVID-19 manifestation occurred. SARS-CoV-2 load at enrollment, shedding on day 15, and antibody responses were also studied. Results: After 28 days of follow-up, 74/113(65%) SARS-CoV-2-infected elders remained asymptomatic. 54% of pre-symptomatic patients developed hypoxemia and ten pre-symptomatic patients died. Dementia was the only clinical risk factor associated with disease(OR 2.41(95%CI=1.08, 5.39). In a multivariable logistic regression model, dementia remained as risk factor for COVID-19 severe disease. Furthermore, dementia status showed a statistically significant different trend when assessing the cumulative probability of developing COVID-19 symptoms(log-rank p=0.027). On day 15, SARS-CoV-2 was detectable in 30% of the asymptomatic group while in 61% of the pre-symptomatic(p=0.012). No differences were observed among groups in RT-PCR mean cycle threshold at enrollment(p=0.391) and in the rates of antibody seropositivity(IgM and IgG against SARS-CoV-2). Conclusions: In summary, 2/3 of our cohort of SARS-CoV-2 infected elders from vulnerable communities in Argentina remained asymptomatic after 28 days of follow-up with high mortality among those developing symptoms. Dementia and persistent SARS-CoV-2 shedding were associated with progression from asymptomatic to symptomatic infection.